2020
DOI: 10.1007/s11240-020-01831-4
|View full text |Cite
|
Sign up to set email alerts
|

Doubled haploid production in onion (Allium cepa L.): from gynogenesis to chromosome doubling

Abstract: Bulb onion ( Allium cepa L.) is an allogamous diploid (2n = 16) important for its culinary uses, nutritional value, and medicinal benefits. Despite its economic importance, onion yields and bulb quality are declining, emphasizing the need for new and improved strategies for maintaining and enhancing overall crop quality. Development of inbred lines in onion through traditional breeding is often difficult due to its biennial life cycle, inbreeding depression, and comparatively high heterozygosities. Moreover, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 135 publications
1
4
0
Order By: Relevance
“…Our results have been consistent with those reported by Doi et al (2011), who examined the gynogenetic responses of six developmental stages of flowers and found that the later stages (just before anthesis or flower anthesis) were more responsive than bud stages in cultivated gentians. These results for gentians are also observed for other crops, of which the explants from just before anthesis or at anthesis (embryo sac is mature) show the highest gynogenic response (Chen et al 2011, Dong et al 2016, Khan et al 2020, Mukhambetzhanov 1997).…”
Section: Discussionsupporting
confidence: 58%
“…Our results have been consistent with those reported by Doi et al (2011), who examined the gynogenetic responses of six developmental stages of flowers and found that the later stages (just before anthesis or flower anthesis) were more responsive than bud stages in cultivated gentians. These results for gentians are also observed for other crops, of which the explants from just before anthesis or at anthesis (embryo sac is mature) show the highest gynogenic response (Chen et al 2011, Dong et al 2016, Khan et al 2020, Mukhambetzhanov 1997).…”
Section: Discussionsupporting
confidence: 58%
“…In the case of self-pollinated species, in vitro culture of unfertilized female gametes is achieved by culturing flower buds prior to anthesis, while in male-sterile or selfincompatible plants it is performed at any stage of ovule development, since they show a favorable response to gynogenic induction [24]. This technique is successfully employed in species of the genus Allium, where it is the main technique to derive DHs [44]. For example, Panahandeh et al [45] achieved a gynogenic induction range of 5 to 12% by culturing unpollinated flower buds of Allium hirtifolium Boiss., which allowed callus formation with a success rate of 20%, of which the efficiency of obtaining haploid plants was 70 to 77%.…”
Section: In Vitro Culture Of Ovaries or Ovulesmentioning
confidence: 99%
“…Establishment of DH lines has accelerated the breeding progress and enhanced the breeding efficiency in many species of land crops (Weber 2014, Ferrie and Caswell 2016, Khan et al. 2020). They can either be used directly for selection of elite lines or serve as the parents of crosses for selection of superior hybrid lines.…”
Section: Discussionmentioning
confidence: 99%